Axonal transport during injury on a theoretical axon - Chandra, Soumyadeep; Chatterjee, Rounak; Olmsted, Zachary T.; Mukherjee, Amitava; Paluh, Janet L. (Frontiers in Cellular Neuroscience, 2023)
In neuronal axons directional transport occurs along a unique network of discontinuous polar microtubule (MT) bundles whose integrity is integral to neurodevelopment, plasticity, and cognition. Axonopathies arise due to brain trauma and genetic diseases that perturb or disrupt the axon MT infrastructure and the dynamic interplay of motor proteins and cargo essential for axonal maintenance and neuronal signaling. Inability to visualize and quantifying normal and altered nanoscale spatiotemporal dynamic events of axonal transport in sufficient detail experimentally prevents a full mechanistic understanding of injury and disease progression or recovery. To address this gap we generated DyNAMO, a Dynamic Nanoscale Axonal MT Organization model that is a biologically realistic theoretical axon framework. We apply DyNAMO to experimentally simulate multi-kinesin traffic response to focused or distributed tractable injury parameters that are MT network perturbations affecting MT lengths and multi-MT staggering. We track kinesins of different motility and processivity, their influx rates, in-transit dissociation and reassociation from inter-MT reservoirs, progression and quantify and spatially represent output ratios of motors. DyNAMO demonstrates in detail the complex interplay of mixed motor types, crowding, kinesin off/on dissociation and reassociation and injury consequences to forced intermingling. Stalled forward progression with different injury states is seen as persistent dynamicity of kinesins transiting between MTs and inter-MT reservoirs. DyNAMO analysis provides novel insights and quantification of axonal injury scenarios and relates these to influences on signaling outputs, including patterns of gating, waves and pattern switching. The DyNAMO model significantly expands the network of heuristic and mathematical analysis of neuronal functions relevant to axonopathies, diagnostics and treatment strategies.